S107 The influence of viral symptoms in infective exacerbations of non-cystic fibrosis bronchiectasis. (2nd December 2011) - Smith, M P; Doherty, C J; Govan, J R W; Templeton, K; Hill, A T
Abstract : Aim: The aim of this study was to determine whether presence of viral symptoms influenced severity or outcome of exacerbations of bronchiectasis. Methods: Patients presenting to our outpatient service with exacerbations of bronchiectasis (defined as increasing cough, increasing sputum volume and worsening sputum purulence) requiring 2 weeks' oral antibiotic therapy were included. Patients reporting viral symptoms (defined as fever and any two of: unusual tiredness, headache, rhinorrhoea, sore throat, anorexia, myalgia, diarrhoea or vomiting) were compared with those who did not. The following outcomes were used to assess the exacerbation and response to 2 weeks' antibiotic therapy between the two groups: sputum bacteriology; sputum colour; 24 h sputum volume; respiratory viral PCR [Influenza A and B; Respiratory Syncytial Virus; Parainfluenza Type 1, 2, 3; Adenovirus]; incremental shuttle walk test; total white cell count; lymphocyte count; neutrophil count; C reactive protein; Erythrocyte Sedimentation Rate. Data is presented as median (IQR) and groups compared using the Mann–Whitney U Test. Results: 40 patients were included. 17 reported viral symptoms. Of the 17 patients who reported viral symptoms, only 2 had positive viral PCR [Influenza Type B (n=1) and Respiratory Syncytial Virus (n=1)]. No patient in the group not reporting viral symptoms had a positive viral PCR. At the start of the exacerbation, there was no significant difference in any parameter between the groups and both groups had a similar and positive impact with 2-week course of antibiotic therapy. Abstract S107 table 1 details the measurements at the start and end of the exacerbation for each group. Conclusion: There was a low prevalence of positive virology despite the presence of viral symptoms and outcomes were similar in patients with and without viral symptoms. Larger cohort studies are needed.